Implementasi Pendidikan Multikultural sebagai Adaptasi Pesantren Bali Bina Insani di Daerah Minoritas Muslim - Qadam, Izah Ulya; Manawi, Ahmad Lutfi; Fathurrozaq, Muhammad; Alfi, Ika Maulidatul; Wahyuni, Hintan Mustika (LP2M IAIN kUDUS, 2022)
There are non-Muslim teachers in the formal education institutions of the BBI Islamic Boarding School. Non-Muslim (Hindu) teachers pass their knowledge on to their students, all of whom are farmers, because the students live in boarding schools. So, in terms of human resources, these farmers do have a multicultural education in various religions. This multicultural education practice is clearly reflected in the management of human resources of the faculty, staff and other educational components. This research is a field study and the author uses a qualitative approach in this research. The authors set the research location in Tabanan, a boarding school in Bina Insani, Bali. The author chose this location because the Bina Insani Islamic Boarding School in Bali is an example of interfaith multicultural education. Based on an analysis of all available literature data, our results show that multicultural education at the Bina Insani Bali Islamic Boarding School aims to instill tolerant attitudes and behaviors among religious people. Pesantren also want to teach students the beauty of tolerance for other religions. Multicultural education at Pesantren Bina Insani (PBBI) Bali is characterized by the presence of elements of education that rely on students and educators as individuals or groups to represent (represent) the community. multiple cultures. Identity is related to the attitude of a person or group of people. They influence each other based on their identity, which includes interactions between different and different cultures.